Refractory Helicobacter pylori infection after standard triple drug therapy: A case report highlighting diagnostic and therapeutic dilemmas - Kotadiya, Smit; Tan, Ernestine Faye; Changela, Madhav; Panigrahi, Kalpana (Eastern Journal of Medical Sciences, 2025)
Helicobacter pylori is a gram-negative bacterium affecting nearly half of the global population and has been proven as a significant risk factor for gastric carcinoma and pathologies related to the stomach, i.e., gastritis, peptic ulcer disease, and MALT (mucosa-associated lymphoid tissue lymphoma). A major concern for managing H. pylori infection is its significantly increasing resistance to guideline-recommended first-line therapy, which is subsequently causing chronic inflammation and an eventual progression to carcinoma. There are several other factors which also affect the possible outcome of the treatments other than antibiotic resistance, i.e., sensitivity and specificity of tests, timing of retesting after eradication therapy, refractory and recurrent infection, and inadequate acid suppression. MALT lymphoma is the most common malignancy associated with H. pylori; on the other hand, its complete remission is possible in more than 50% of cases after eradicating therapy. This case report is of a middle-aged woman who had continued positive antigen testing even after completion of standard guideline-recommended three different regimens for H. pylori infection. After the third regimen, mild symptom improvement was reported, and there was a negative result for biopsy obtained through EGD despite a positive antigen test, as mentioned before. This complexity in management emphasizes how difficult it is to treat recurrent infection and the importance of knowledge of the recommended guidelines to achieve eradication. Simultaneously, there is always an increasing chance of chronic inflammation as symptoms are lasting longer due to a delay in eradication. Therefore, early treatment after diagnosis must be considered. Shared decision making, compliance with therapy, hand hygiene, breaking the chain of transmission between intrafamilial members, and health education are also crucial steps in management.